TRANSLATION IDEOLOGY OF FRENCH NOVELS INTO INDONESIAN IN COLONIAL AND POST-COLONIAL PERIOD - Sajarwa Sajarwa (Journal of Applied Linguistics and Literature)
This study analyzes the differences in the expression of meaning of the colonial and postcolonial French novels and the ideology of translating French novels into Indonesian during the colonial and postcolonial periods. This study uses data from French novels and their translations into Indonesian during the colonial and postcolonial periods. The data were analyzed by using descriptive-qualitative-comparative method. The results of this study show that text message expression during colonial period is indirect due to at that time The society was under the rule of the Dutch colonialists or subaltern. In post-colonial period, the community social situation changed, people were no longer afraid to express their thoughts or they were more open so that the delivery of meaning is direct. Colonial period novels have two types of foreignization ideology, namely self-names translation and setting translation, while post-colonial period novels have three types, namely self-names translation, title translation, and setting translation. The novels domestication ideology during colonial period occurred in translation of pronouns on and the translation of kinship calls, while in post-colonial period novels it occurred in pronouns on translation, kinship calls translation, and self-names translation. The different ideology in the two novels is self-names translation.